Topological pumping of photons in nonlinear resonator arrays - Tangpanitanon, J; Bastidas, V; Al-Assam, S; Roushan, P; Jaksch, D; Angelakis, D (American Physical Society, 2016)
We show how to implement topological or Thouless pumping of interacting photons in one dimensional nonlinear resonator arrays, by simply modulating the frequency of the resonators periodically in space and time. The interplay between interactions and the adiabatic modulations enables robust transport of Fock states with few photons per site. We analyze the transport mechanism via an effective analytic model and study its topological properties and its protection to noise. We conclude by a detailed study of an implementation with existing circuit QED architectures.